FORMULATION AND EVALUATION OF MUCOADHESIVE MICROSPHERES OF LAMIVUDINE (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The aim of the present work was to prepare and evaluate mucoadhesive microspheres of Lamivudine. Microspheres were formulated using sodium alginate (5%) with mucoadhesive polymer (Chitosan 1%) and copolymer Sodium CMC HPMC, Xanthan gum (XG) in concentration of 1% (Chitosan1% + HPMC1%) (1%) retarding agents and 10% of Calcium chloride (CaCl2), Aluminum sulphate (AlSO4) as cross linking agents by employing Ionic Gelation Technique. The particle size was characterized for by scanning electron microscopy (SEM) and drug excipients compatibility was determined by FT-IR spectroscopy. Percentage drug content, Entrapment efficiency and in-vitro dissolution studies were also carried out. Among the prepared microspheres (F8) formulation in which AlSO4 was used as cross linking agent, portray better sustained release for more than 12hrs. The dissolution profile followed the near zero order profile and Hixon-crowell as “best fit” model. SEM shows that prepared microspheres were of spherical in shape and free flowing. FT-IR results showed compatibility of Lamivudine with excipients used.